Pengaruh Label Halal terhadap Minat Beli dengan Religiositas sebagai Variabel Moderasi (Kajian Konsumen Kuliner di Kota Banda Aceh) - Havna Havna; Azharsyah Ibrahim; Muhammad Arifin (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the effect of halal labeling on consumer purchase intention in the culinary sector in Banda Aceh City, with religiosity as a moderating variable. In the context of a society that upholds Islamic law values, the halal status of products is often socially assumed, so the presence of a halal label is not always a primary consideration in purchasing decisions. This study employs a quantitative approach using a survey method involving 384 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The results indicate that halal labeling has a positive and significant effect on purchase intention (β = 0.171; p < 0.05). Additionally, religiosity is proven to significantly moderate the relationship between halal labeling and purchase intention in a negative direction (β = -0.080; p < 0.05), indicating that religiosity weakens the influence of halal labeling on purchase intention. These findings suggest that consumers with higher levels of religiosity tend to rely less on halal labels when determining their purchase intention, as the halal status of products is already socially assumed. This study highlights that the effectiveness of halal labeling is contextual and influenced by the level of consumer religiosity.